How Civic Education Strategies Shape the Internalization of National Character: Evidence from Mixed Methods in Islamic Junior High Schools - Ali Iskandar Zulkarnain; Gito Supriadi (At- Ta'lim : Jurnal Pendidikan, 2026)
This study examines how Civic Education (PKn) instructional strategies shape the internalization of national character among students in an Islamic junior high school context. Employing a convergent parallel mixed-methods design, quantitative data were collected from 135 students using a Likert-scale questionnaire and analyzed through descriptive statistics, Pearson’s correlation, and one-way ANOVA. Qualitative data were gathered through interviews, classroom observations, and document analysis, and analyzed thematically. Quantitative results indicate a high overall level of national character internalization (M = 4.12), with love for the homeland (M = 4.32) and tolerance (M = 4.21) emerging as the strongest dimensions, while practical nationalism (M = 3.89) remains comparatively lower. A statistically significant moderate positive correlation was found between instructional strategies and national character internalization (r = 0.46, p < .05), alongside significant differences across grade levels (F = 2.87, p = .042), with higher internalization among Grade IX students. Qualitative findings explain these patterns by showing that participatory and experiential strategies such as discussions, simulations, and project-based learning, effectively foster students’ affective engagement and moral reflection, yet opportunities for sustained behavioral enactment remain limited. The findings conceptualize national character internalization as a differentiated process encompassing moral knowing, moral feeling, and moral action, where instructional strategies more strongly influence affective commitment than consistent civic behavior. Theoretically, this study contributes to citizenship education scholarship by refining the multidimensional understanding of value internalization. Practically, it highlights the need for inclusive and experience-based pedagogical approaches supported by structured opportunities for real-world civic practice in religious secondary schools.